PERSEPSI PELANGGAN TERHADAP KUALITAS PELAYANAN DI PT. SMEVA HOLIDAY TOUR AND TRAVEL PEKANBARU - Ansyar, Afifah Fatin; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Competition to dominate market share makes business people to aggressively carry out service processes for their company's products or services so as not to experience a significant decline. This study aims to determine (1) Customer Perceptions of Service Quality at PT. Smeva Holiday Tour and Travel Pekanbaru. (2) To find out the Constraints in Service Quality management at PT. Smeva Holiday Tour and Travel Pekanbaru. This research is a descriptive quantitative study with respondents consisting of 50 customers who use the services of PT. Smeva Holiday Tour and Travel Pekanbaru. Determination of respondents with accidental sampling. Data collection is done by observation, questionnaires, interviews and documentation. Data analysis techniques used in the interval distribution method are grouping data into several categories that show a lot of data in each category and and each data is entered into two or more categories. The results of this study indicate that customer perceptions affect the quality of service provided is good. This is inseparable from the efforts made by the management in maintaining service quality. Keywords: Customer Perception, Service Quality, PT. Smeva Holiday Tour and Travel Pekanbaru